Dermoid sinus in a Great Pyrenees dog - Camacho, Aparecido Antônio; Laus, José Luiz; Valéri, Victório; Valéri, Fábio Valiengo; Nunes, Newton (Brazilian Journal of Veterinary Research and Animal Science, 1995)
In the scientific literature this is the first case of dermoid sinus described in a Great Pyrenees dog. The diagnosis was made on the basis of anamnesis and dermatology and histopalology findings. The clinical management was exeresis of the sinus, the owners being informed about the congenital hereditary characteristics of the disease. Six months after surgery the animal was reevaluated on the during several return visits and no dermatologic lesion was detected.